Assessment of a couple-based HIV prevention intervention and associations between relationship quality and sexual risk behavior in Uganda - Ruark, A; Kajubi, P.; Ruteikara, S.; Green, E.C.; Hearst, N. (AIDS and behavior, 2018)
Despite evidence that a greater focus on couples could strengthen HIV prevention efforts, little health-related research has explored relationship functioning and relationship quality among couples in Africa. Using data from 162 couples (324 individuals) resident in a peri-urban Ugandan community, we assessed actor and partner effects of sexual risk behaviors on relationship quality, using psychometric measures of dyadic adjustment, sexual satisfaction, commitment, intimacy, and communication. For women and men, poor relationship quality was associated with having concurrent sexual partners and suspecting that one’s partner had concurrent sexual partners (actor effects). Women’s poor relationship quality was also associated with men’s sexual risk behaviors (partner effects), although the inverse partner effect was not observed. These findings suggest that relationship quality is linked to HIV risk, particularly through the pathway of concurrent sexual partnerships, and that positive relationship attributes such as sexual satisfaction, intimacy, and constructive communication can help couples to avoid risk.
Keywords: HIV prevention, behavior change, couple relationship quality, concurrent sexual partnerships, alcohol